Exploring the impact of the physical conditions of mannequin displays on mental simulation: An embodied cognition theory perspective - Yim, Mark Yi-Cheon; Lee, JeongGyu; Jeong, Haeyoung (Journal of retailing and consumer services, 2021)
This study examines how mannequins' physical conditions of display height and distance are related to consumers’ shopping motivations in generating mental simulation resulting in purchase intention. A 2 × 2 x 2 between-subjects lab experiment (n = 249) was conducted to address this question. The results reveal a significant three-way interaction effect of display height, distance, and shopping motivation. Specifically, it is found that for those with a dominant hedonic shopping motivation, a mannequin displayed up high generates greater mental simulation than one displayed down low, but for those with a dominant utilitarian shopping motivation, a mannequin displayed high and close to consumers generates greater mental simulation than one displayed low and close to them. This study also reveals that mental simulation mediates the influence of the interaction effect of “display height x distance,” moderated by shopping motivation, on purchase intention. Important theoretical and practical implications for retail managers are discussed. •For hedonic consumers, a mannequin placed high generates greater mental simulation than one displayed low.•For utilitarian consumers, a mannequin displayed close and high generates greater mental simulation than one displayed low.•For utilitarian consumers, a mannequin’s display height does not affect mental simulation, when it is displayed far.•Mental simulation mediates the interaction effect of mannequin display and shopping motivation on purchase intention.